Hubungan Strategi Koping Dengan Kepuasan Hidup Lansia Di Panti Bhakti Luhur Sidoarjo - Rustini, Sri Anik; Widyastuti, Merina; Sari, Ninik Ambar; Nurhayati, Ceria (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2021)
Introduction: The increased elderly population will have an impact on various aspects of life. The problem faced by the elderly is welfare that has impact on elderly life satisfaction. Individual coping as an action-oriented and intrapsychic effort to control and dominate. Objectives: The purpose of this study was to analyze the relationship between coping strategies and elderly life satisfaction at Panti Bhakti Luhur Sidoarjo. Methods: Analytical observational research design with cross-sectional approach. The sampling technique uses non-probability sampling with accidental sampling. The population of this study was 108 people and the research sample was 85 elderly aged over 60 years at Panti Bhakti Luhur Sidoarjo. To assess coping strategies using the WOC (Ways of Coping Questionnaire) questionnaire, to assess life satisfaction using the SWLS (Satisfaction With Life Scale) questionnaire. The data were then tested using the Spearmen Rho Correlation. Results: The results showed a relationship between coping strategies and life satisfaction of 0.001 (Ï <0.05). Conclusions: Â The implication of this study is that coping strategies are related to elderly life satisfaction. Support from families and related agencies is needed to help elderly coping strategies to increase life satisfaction by motivating and providing emotional assistance to the elderly.